Studi Karakteristik Mekanik Dan Struktur Mikro Coran Aluminium Minuman Kaleng - Latif Kuncoro Wasmi Apris; Dedy Masnur; M Dalil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Scrap aluminum cans recycle processing through metal casting is a way to improve the economic value. Yet, this process could not instantly be carried out to produce parts without knowing the chararacteristics of mechanical and microstructure. This study investigates those characteristics in three different pour temperatures, 650°C, 700°C, and 750°C respectively and three die temperatures, 100°C, 200°C, and 300°C. The result showed that the hardness number of aluminum cast was decreased as well as increasing of pours and die temperatures. The highest hardness number was 67.615 VHN at 650°C pour temperature, but the lowest one was 58.327 VHN at 750°C pour temperature. The highest hardness number was 77.871 VHN at 100°C die temperature, but the lowest was 61.479 VHN at 300°C die temperature. Tensile strength values were increased at a pour temperature of 650°C to 700°C and decreased at pour temperature of 750°C. The highest tensile strength was 174.183 MPa at 700°C pour temperature and the lowest tensile strength was 110.900 MPa at 750°C pour temperature. The tensile strength was decreased as well as increasing of die temperature. The highest tensile strength was 177.473 MPa at 100°C die temperature and the lowest tensile strength was 108.317 MPa at 300°C die temperature. The microstructure results showed that at650°C pour temperature and 100°C die temperature with more thick flake lines (Mg) than thin flake lines (Mg). The 700°C pour temperature and 200°C die temperature had with more dominant thick flake lines (Mg) than thin flake lines (Mg). The 750°C pour temperature and 300°C die temperature had with more dominant thin flake lines (Mg) than thick flake lines (Mg).Keywords: Hardness, Tensile Strength, pour temperatures, die temperatures, microstructure